New insights into the structure of (1→3,1→6)-β-D-glucan side chains in the Candida glabrata cell wall. - Douglas W Lowman; Lara J West; Daniel W Bearden; Michael F Wempe; Trevor D Power; Harry E Ensley; Ken Haynes; David L Williams; Michael D Kruppa (PLoS ONE)
β-Glucan is a (1→3)-β-linked glucose polymer with (1→6)-β-linked side chains and a major component of fungal cell walls. β-Glucans provide structural integrity to the fungal cell wall. The nature of the (1-6)-β-linked side chain structure of fungal (1→3,1→6)-β-D-glucans has been very difficult to elucidate. Herein, we report the first detailed structural characterization of the (1→6)-β-linked side chains of Candida glabrata using high-field NMR. The (1→6)-β-linked side chains have an average length of 4 to 5 repeat units spaced every 21 repeat units along the (1→3)-linked polymer backbone. Computer modeling suggests that the side chains have a bent curve structure that allows for a flexible interconnection with parallel (1→3)-β-D-glucan polymers, and/or as a point of attachment for proteins. Based on these observations we propose new approaches to how (1→6)-β-linked side chains interconnect with neighboring glucan polymers in a manner that maximizes fungal cell wall strength, while also allowing for flexibility, or plasticity.